Rethinking procedural pain in labor: A comparison of lidocaine injection techniques for epidural catheter placement assessed with an objective clinician-centric pain score—A double-blind randomized controlled trial - Lukas Croner; Plato Lysandrou; Haosheng Li; Andrew Devine; Tyler Balon; Yun Xia; Nasir Hussain; Yue Yu; Mahmoud Abdel-Rasoul; Marco Echeverria Villalobos; Alberto Uribe; Elvia Vera Miquilena; et al. (PLoS ONE, 2026)
Introduction Local lidocaine infiltration before Tuohy needle insertion is essential for epidural analgesia. Lidocaine can be administered intradermally or subcutaneously, but the technique that causes less pain for laboring patients is unclear. Pain is typically assessed using the subjective Numeric Rating Scale (NRS), while the Critical-Care Pain Observation Tool (CPOT) offers an objective alternative, evaluating facial expressions, body movements, muscle tension, and vocalizations. This pilot study compared subcutaneous (SC) and intradermal (ID) lidocaine administration to evaluate lidocaine injection pain and its analgesic efficacy. Methods In this double-blind randomized trial, laboring parturients received 3 mL of 1% lidocaine via SC (90-degree angle) or ID (60-degree angle) injection using a one-inch 25G needle. Primary outcomes included procedural pain during lidocaine administration, assessed using CPOT (clinician-centric) scores. Secondary outcomes encompassed lidocaine’s analgesic efficacy during Tuohy needle insertion with both CPOT and NRS, hemodynamic stability, patient satisfaction, and NRS for two lidocaine injection techniques as references. Results Fifty-one patients were randomized into the SC Group (n = 26) and the ID Group (n = 25). No significant differences were observed in overall CPOT or NRS scores between groups, but SC administration yielded significantly lower muscle tension scores (Krushkal-Wallis test p = 0.018). The analgesic efficacy on Tuohy needle insertion, patient satisfaction, and hemodynamic values was not significantly different between the two techniques. A weak correlation between CPOT and NRS scores (Spearman’s r = 0.32, p = 0.024) highlighted the complementary roles of objective and subjective, patient-centric, pain assessments. There was no statistical significance of interobserver variation for CPOT assessment. Conclusion This pilot trial establishes proof of concept for validating the CPOT in obstetric settings and highlights both the need for and feasibility of future studies aimed at optimizing lidocaine administration protocols during labor epidural placement. While this study found no global differences in pain scores between subcutaneous and intradermal lidocaine, subcutaneous injections demonstrated less muscle tension with similar analgesic efficacy. The discordance between CPOT and NRS underscores the value of integrating both tools for comprehensive procedural pain evaluation.